Zinc deficiency as risk factor for stunting among children aged 2-5 years - Bening, Salsa; Margawati, Ani; Rosidi, Ali (Universa Medicina, 2017)
BackgroundStunting is a nutritional problem in the form of linear growth disturbance caused by low intake of macro- and micronutrients. The prevalence of stunting in children aged 2-5 years in Semarang is higher in well-to-do families (67.2%) than in poor families (32.8%). The purpose of this study was to analyze the role of low adequacy levels of vitamin C, iron, zinc and low food expenditure as risk factors of stunting among children aged 2-5 years. MethodsThis was a case-control study with a sample of 71 cases (stunting) and 71 controls (no stunting). The collected variables were adequacy levels of vitamin C, iron, zinc and level of food expenditure. Nutrient intake data were obtained with the semiquantitative food frequency questionnaire (FFQ), while data on food expenditure were obtained through a food expenditure questionnaire. Data analysis was performed using simple and multivariate logistic regression method. ResultsThe results of the simple logistic regression showed that low levels of vitamin C ( OR=2.97; 95% CI=1.41 – 6.31), iron (OR=2.87; 95% CI=1.44 – 5.71) and zinc (OR=9.24; 95% CI=2.02 – 42.12) were risk factors of stunting. Multivariate analysis showed that the risk factor that most affected stunting was a low level of zinc (OR=6.39; 95% CI=1.34 – 30.33). A low level of food expenditure was not proven to influence the incidence of stunting. ConclusionsA low level of zinc was the risk factor that most affects stunting in children aged 2-5 years. Preventive strategies to prevent stunting and promote healthy eating is recommended.